Exsistentia non est realitas: La tesis de Kant sobre el ser - Lema Hincapié, Andrés (2014)
For Immanuel Kant existence and reality are not interchangeable. In this way, Kant is following a long medieval tradition. Here I am presenting some precise indications about philosophical terms in order to better understand what Martin Heidegger called the Kantian thesis on being. I begin by studying the synonymy of some words and the conceptual differences between them. This allows the reader to reach a deeper comprehension of two works by Kant: The Only Possible Argument in Support of a Demonstration of the Existence of God (1763) and the Critique of Pure Reason (1781, 1787). Then, I analyze some of Kant’s fragments in German by contrasting them to their Spanish, French, and English translations. I also include references to the Latin translation of the Critique of Pure Reason. Finally, I show that the already canonical translations of Kant’s works unfor- tunately are often wrong, since he consistently distinguishes between existence and reality. On the contrary, such translations are not consistent and misinterpret Kant’s thought concerning those central notions.